2023
DOI: 10.1021/acsaem.2c03059
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Current Heterogeneity at the Interface between a Lithium Electrode and Polymer/Ceramic Composite Electrolytes

Abstract: Although lithium metal anodes are expected to increase the energy density of next-generation batteries, dendrite growth during charge remains a major bottleneck preventing widespread implementation. Composite solid electrolytes with ceramic particles embedded in a polymer matrix have the potential to prevent dendrites owing to the higher mechanical stiffness while also possessing the flexibility to maintain contact with the electrode. However, microscopically, the different mechanical and electrochemical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…Figure a shows the idealized BLM microstructure compared to dense statistically modeled twin microstructures for sintering times ranging from 2 to 8 h. Apparently, the deviation of the actual microstructure from that assumed in the BLM increases with sintering time, as the size and shape of individual grains vary more with longer sintering times. This behavior has a major effect on ion transport through the material and, thus, on the performance of a device where the material is incorporated Figure b depicts a cross-section of the direct current (DC) distribution in the transport plane for the different microstructures.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure a shows the idealized BLM microstructure compared to dense statistically modeled twin microstructures for sintering times ranging from 2 to 8 h. Apparently, the deviation of the actual microstructure from that assumed in the BLM increases with sintering time, as the size and shape of individual grains vary more with longer sintering times. This behavior has a major effect on ion transport through the material and, thus, on the performance of a device where the material is incorporated Figure b depicts a cross-section of the direct current (DC) distribution in the transport plane for the different microstructures.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior has a major effect on ion transport through the material and, thus, on the performance of a device where the material is incorporated. 71 Figure 5b depicts a cross-section of the direct current (DC) distribution in the transport plane for the different microstructures. The highly symmetric grain arrangement in the BLM features 1D transport, which is indicated by a homogeneous current distribution in the system.…”
Section: Revealing the Effect Of The Microstructure On The Blm Analys...mentioning
confidence: 99%
“…68 Recent computational modeling predicted that ceramic ordering at the lithium metal interface in composites can lead to heterogeneous lithium plating due to uneven Li + transport, and that a polymer interlayer at the interface�as fabricated from our composite production process�is one solution to this issue for even lithium plating. 74 Keeping in mind these nuances of inherently heterogeneous CPEs, any significant benefits from ionic conductivity and dictated lithium deposition should lead to more homogeneous, dense lithium deposits that should be easily stripped on discharge. This would lead to increased CE over many cycles, limiting lithium inventory loss and extending battery lifetime.…”
Section: Effect Of Fiber Loading On Ce and Ccd Our Resultsmentioning
confidence: 99%
“…Lithium deposition with separators having pores parallel to the electrode surface, analogous to aligning nanofibers in planes against the electrode, is predicted to control dendrite formation and even revive dead lithium depending on the separator dimensions . Recent computational modeling predicted that ceramic ordering at the lithium metal interface in composites can lead to heterogeneous lithium plating due to uneven Li + transport, and that a polymer interlayer at the interfaceas fabricated from our composite production processis one solution to this issue for even lithium plating …”
Section: Results and Discussionmentioning
confidence: 99%
“…While dispersing ceramic particles within a polymer can deter its crystallinity, particle agglomerations, inhomogeneity at the lithium metal interface, and ceramic-polymer incompatibility are challenges. , It was found that the portion of amorphous polymer is responsible for ionic transport in hybrid composite separators. ,, The separators with larger amorphous polymer fractions had good interfacial compatibility with the particles and maximal interfacial area across those domains owing to fewer agglomerations . One composite nanostructure in particular has the potential to completely avoid polymer crystallinity, particle agglomerations, and interface heterogeneity .…”
Section: Introductionmentioning
confidence: 99%